The relation between running speed and measures of strength and power in professional rugby league players - Baker, D.; Nance, S. (The Journal of Strength and Conditioning Research, 1999)
The purpose of this study was to investigate the relation between running speed and a number of common strength and power tests, in absolute terms and relative to body mass. Twenty professional rugby league players were assessed for 10- and 40-m running speed, maximum strength in a 3 repetition maximum (RM) squat and 3RM power clean from the hang, and leg power. Power was assessed by the Plyometric Power System (PPS) during barbell jump squats with loads of 40, 60, 80, and 100 kg. The results indicated that, while 10- and 40-m sprint performances are highly related (r = 0.72, p 0.05), there still remains considerable variation in the factors that contribute to performance over each sprint distance. Although no absolute strength or power score was significantly related to either sprint performance, almost all the scores relative to body mass were significantly related to sprint performance. For the 10-m sprint, the significant relations ranged from r = 0.52 to r = 0.61 (p 0.05). For the 40-m sprint, the significant relations ranged from r = 0.65 to r = 0.76 (p 0.05). On the basis of this research, professional rugby players may need to be trained differently to a certain extent for 10- and 40-m sprint capabilities, as the longer distances appear more reliant on stretch-shortening cycle performance.